2015
DOI: 10.1164/rccm.201503-0516oc
|View full text |Cite
|
Sign up to set email alerts
|

Early High-Volume Hemofiltration versus Standard Care for Post–Cardiac Surgery Shock. The HEROICS Study

Abstract: For patients with post-cardiac surgery shock requiring high-dose catecholamines, the early HVHF onset for 48 hours, followed by standard volume until resolution of shock and recovery of renal function, did not lower Day-30 mortality and did not impact other important patient-centered outcomes compared with a conservative strategy with delayed CVVHDF initiation only for patients with persistent, severe acute kidney injury. Clinical trial registered with www.clinicaltrials.gov (NCT 01077349).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
155
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(159 citation statements)
references
References 51 publications
2
155
1
1
Order By: Relevance
“…Several studies have examined the timing of RRT initiation in AKI patients in the ICU. It is unclear whether the early initiation of RRT improves survival and renal recovery rates [4][5][6][7][8][9]. These studies, however, differ in their definition of early and late initiation.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have examined the timing of RRT initiation in AKI patients in the ICU. It is unclear whether the early initiation of RRT improves survival and renal recovery rates [4][5][6][7][8][9]. These studies, however, differ in their definition of early and late initiation.…”
Section: Reviewmentioning
confidence: 99%
“…Until recently, three randomized controlled trials (RCTs) evaluated whether the early initiation of RRT improved mortality in patients with AKI [4,5,9]. In one study, Bourman et al randomized 106 critically ill patients with AKI into three groups, 35 were treated with early high-volume HF (HVHF), 35 with early low-volume HF, and 36 with late low-volume HF [4].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the negative results of the IVOIRE trial, Quenot et al found no benefit of the CASCADE technique, allowing very high volume hemofiltration, in a pilot study randomizing 60 patients [17], while Combes et al found no benefit of high volume hemofiltration randomizing 224 patients with postcardiac surgery shock [18]. Finally, Payen and colleagues found no benefit of polymyxin (PMX) hemoperfusion in 232 adult postoperative patients with documented peritonitis and septic shock [19].…”
Section: Extracorporeal Blood Purificationmentioning
confidence: 95%
“…For example, the timing of RRT initiation in the ELAIN Trial is most similar to that in the High Volume Venovenous Hemofiltration Versus Standard Care for Post-Cardiac Surgery Shock (HEROICS) Trial, but the results are discordant. The HEROICS Trial was a multicenter, randomized trial of 224 patients with severe shock requiring high-dose catecholamine infusion after cardiac surgery that compared a strategy of 48 hours of HVHF initiated within 3-24 hours of surgery followed by conventional CVVHDF with standard care, in which CVVHDF was provided only for stage 3 AKI, a BUN.100 mg/dl, or life-threatening hyperkalemia (23). 111 of 112 patients in the early HVHF arm initiated RRT within 24 hours of surgery, whereas 64 of 112 patients in the conventional CVVHDF arm initiated RRT after a mean of 1.563.4 days.…”
mentioning
confidence: 99%